Accounting for Cross-border Mergers and Its Problems - Hana Vomáčková (European Financial and Accounting Journal, 2010)
Both the legal and accounting conceptual differences in national legislations regulating mergers may be quite significant in spite of the unification processes taking place via the transposition of EU directives into national law. Most often, we find differences in the following issues: If there is a re-measurement or no re-measurement during mergers, and where re-measurement is required, the manner of its reflection in the accounting records in accordance with national regulations, usually as a modification of a general accounting method used for a purchase; The date of acquisition (balance sheet date) versus the date of coming into force by means of an entry in the prescribed register; The existence or non-existence of a duty to prepare special purpose financial reports whose consolidation is used to determine values in the opening balance sheet of the legal successor of a merger of the businesses of the participating companies; The determination of an opening balance sheet by consolidating the special purpose financial reports or the participating companies, but – technically – by means of accounting entries by which the successor takes over the business of a liquidated company and its assets and liabilities, i.e. a de facto accounting procedure as used for booking the contribution of a business. From a formally legal point of view, these discrepancies represent obstacles in implementing crossborder mergers. If we do not take into consideration potentially inaccurate terminology arising from the translation of the EU directive regulating cross-border mergers, there is a solution based on the direction implied already in the 1980's by International Accounting Standards, i.e. to understand both domestic and cross-border mergers as business combinations and to build both commercial law and accounting law for this area on the common concept whose expression is a de facto general accounting method used for purchases.
Keywords: M41; 650; Merger; Cross-border mergers; Date of acquisition; Date of balance sheet; Special purpose financial reports; Opening balance sheet; Measurement by merger; Fair value; Book value; Gains of new measurement